Risk Factors for Aspergillus Colonization and Allergic Bronchopulmonary Aspergillosis in Children With Cystic Fibrosis - V. Jubin; Stéphane Ranque; Nathalie Stremler le Bel; Jacques Sarles; J.‐C. Dubus (2010)
The annual prevalence of Aspergillus colonization (AC) and allergic bronchopulmonary aspergillosis (ABPA) has recently increased in pediatric patients with cystic fibrosis (CF). The reasons remain unclear although a number of factors have been suggested to be involved. This study was set up to investigate the association between potential predisposing factors, including new therapies recommended in CF, and the occurrence of AC or ABPA in children with CF.The medical records of 85 children monitored regularly in the Pediatric Reference Centre for Cystic Fibrosis Care (RCCFC) of the University Hospital of Marseille (France) were analyzed from the first time they attended the RCCFC until either the occurrence of an end event, or their last visit to the RCCFC. Risk factors for AC or ABPA were analyzed by univariate and multivariate logistic regression.Eight children developed ABPA and 18 had AC. In univariate analysis, ABPA was significantly associated with RhDNase therapy, sensitization to Alternaria and Candida, and a low body mass index (BMI). Multivariate analysis identified an independent association between low BMI and ABPA (OR = 10.6, 95% CI [2.2-51.8], P = 0.004), and for the first time, between long-term azithromycin therapy and AC (OR = 6.4, 95% CI [2.1-19.5], P = 0.001). This latter association might be explained by the inhibitory effect of azithromycin on both the recruitment and the activation of neutrophils, which represent the first-line defenses against Aspergillus.The risk factors associated with AC and ABPA in children with CF identified in this comprehensive exploratory study now need to be confirmed in further prospective studies.